2020
DOI: 10.1123/jsr.2019-0345
|View full text |Cite
|
Sign up to set email alerts
|

Pain Education With Therapeutic Exercise in Chronic Nonspecific Low Back Pain Rehabilitation: A Critically Appraised Topic

Abstract: Clinical Scenario: Low back pain is widely prevalent in the general population as well as in athletes. Therapeutic exercise is a low-risk and effective treatment option for chronic pain that can be utilized by all rehabilitation clinicians. However, therapeutic exercise alone does not address the psychosocial aspects that are associated with chronic low back pain. Pain education is the umbrella term utilized to encompass any type of education to the patient about their chronic pain. Therapeutic exercise in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…16 The purpose of a biopsychosocial evaluation is to gain a holistic view of the patient's presentation, identify any impairments across health dimensions, and guide a holistic treatment plan, which can help the clinician promote pain neuroscience education. 16,17 Educating the patient on their pain could be an effective treatment strategy. Jones et al 17 found that patients who had pain education in addition to therapeutic exercise showed the greatest improvements in self-reported pain.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The purpose of a biopsychosocial evaluation is to gain a holistic view of the patient's presentation, identify any impairments across health dimensions, and guide a holistic treatment plan, which can help the clinician promote pain neuroscience education. 16,17 Educating the patient on their pain could be an effective treatment strategy. Jones et al 17 found that patients who had pain education in addition to therapeutic exercise showed the greatest improvements in self-reported pain.…”
Section: Main Findingsmentioning
confidence: 99%
“…16,17 Educating the patient on their pain could be an effective treatment strategy. Jones et al 17 found that patients who had pain education in addition to therapeutic exercise showed the greatest improvements in self-reported pain.…”
Section: Main Findingsmentioning
confidence: 99%
“…Medical treatments and physiotherapy are recommended to treat and resolve issues associated with cNLBP [ 3 ]. Therapeutic exercise and manual therapy have a lower risk of increasing future back injuries or work absence and are more effective treatment options for chronic pain than medication or surgery, and they can be performed at rehabilitation clinics [ 4 6 ]. Exercise therapy is a widely used strategy to cope with low back pain that includes a heterogeneous group of interventions ranging from aerobic exercise or general physical fitness to muscle strengthening and various types of flexibility and stretching exercises [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a study on knowledge about the triggers of cLBP, only 3% of the professionals involved in the therapeutic approach to pain point to psychological factors as the main determinant [3]. Therefore, we thought that the identification of psychological reactions in the process of physiotherapy care for patients with chronic cLBP is necessary to identify and differentiate the different clinical profiles that serve as a basis for maximizing treatment results [11][12][13]. The purpose of our study was to describe and quantify the linear association between pain intensity and different psychological variables in patients suffering from cLBP.…”
Section: Introductionmentioning
confidence: 99%